Pengaruh Fasilitas Kerja dan Motivasi Kerja Terhadap Kinerja Karyawan PR. Dua Dewi Cabang Kediri - Rochim, Angga Dika Taufik; Suwarsono, Bambang; Kurniawan , Brahma Wahyu (Universitas Maritim AMNI Semarang, 2023)
The aim of this research is to determine the significance of the influence between work facilities and work motivation both partially and simultaneously. Population in this research totaled 212, the sampling technique used was proportionate stratified random sampling using the isaac and michael table so that 131 samples were found. Method the analysis used is quantitative with inferential statistic. Based on partial test it was found that there was a positive and significant influence between work facilities and employee performance. Work motivation has an insignificant effect and has a negative value on the employee performance of PR.Dua Dewi Cabang Kediri.